The Effect of Transformational Leadership on Gojek Organizational Culture on Driver Partner Work Flexibility - Asmawati, A.; Zahara, Chintya; Wahjono, Sentot Imam (Manunggal Halim Jaya, 2025)
Indonesia's annual digital economic growth of 11% encourages Gojek to create an inclusive work ecosystem for more than 3.1 million driver partners. This study analyzes the influence of transformational leadership on Gojek's organizational culture and its impact on driver partner performance. The method used is a qualitative case study analyzing various written sources, including scientific articles, books, credible opinions, and company policy documents. The results showed that Gojek's transformational leadership succeeded in forming an inclusive and collaborative organizational culture, thus increasing the motivation and performance of driver partners. However, the work flexibility offered still faces challenges in the form of income uncertainty. This study recommends a performance-based incentive system and reward-based training to balance flexibility with optimal performance achievement. The findings are expected to serve as a practical reference for companies in creating a productive and sustainable work environment.